Samba de pareia pelos saberes do corpo que samba - Silva, Jonathan Rodrigues (2019)
The focus of observation of this dissertation is the Samba de Pareia coming from the quilombola community Mussuca, located in Laranjeiras, Sergipe. Samba is mainly performed by women, with the participation of men focused on musical performance, especially on the drum. Other instruments such as ganzá and cuíca are played by the women who sing and come together to celebrate the birth of a child in the community. The dance takes place in a circle, with choreographic variations in pairs. Currently, Samba de Pareia also performs as a show in cultural events that take place outside the community. Through a methodological approach focused on experience (MACEDO, 2015), I conducted the field research becoming a resident of Mussuca. Contact with the researched phenomenon occurred with the daily contact with samba women, including observations, informal conversations, interviews and daily sharing including fishing work and samba parties. The voices of the members, through my capture, choice and writing, make up a significant part of the dissertation text. The reflections on the performing arts and popular cultures and the Samba de Pareia (DUMAS, 2016; OLIVEIRA, 2007; SANTOS, 2017; SILVA, 2015), besides being based on the reality that I lived in Mussuca, dialogue with theoretical studies located in the field of decolonization (DUSSEL, 2013; KILOMBA, 2017; MBEMBE, 2019), racial socio-historical and ethnic issues (AKOTIRENE, 2018; ALMEIDA, 2018; DAVIS, 2016; FANON, 2008; HALL, 2003; HOOKS, 2005; NASCIMENTO, 2018; SOUZA, 2018; SOUZA, 1983). The perceived and analyzed reality expanded with the knowledge I had of the daily reality of women who do the Samba de Pareia, providing a deeper understanding and understanding not only of bodies that sambam, but that work, exist and resist.